2011
DOI: 10.1002/jobm.201100211
|View full text |Cite
|
Sign up to set email alerts
|

Effects of long‐term fertilization on the diversity of bacterial mercuric reductase gene in a Chinese upland soil

Abstract: Soil mercury (Hg) pollution has received considerable attention due to its neurotoxin effects and its potential risk to food safety. The microbial transformation of Hg plays a key role in reducing Hg toxicity by the mercuric reductase (MerA) conferred by genes arranged in the mer operon. This study investigated the effects of long-term fertilization on the diversity of bacterial mercuric reductase gene (merA), which specify the reduction of ionic Hg²⁺ to the volatile elemental form Hg⁰, in an agricultural soil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 33 publications
0
5
0
Order By: Relevance
“…Most Hg in soil is detected as ionic Hg 2+ species and shows relatively low toxicity, however, it still poses some environmental risk due to potential for Hg methylation followed by bioamplification in soilplant systems (Meng et al 2010;Liu et al 2012). Earlier studies have examined microbial methylation of Hg in estuarine, wetland, and freshwater sediments (Gilmour et al 1992; Heyes et al 2006;Duran et al 2008;Todorova et al 2009), but little attention to date has been paid to the linkage between specific types of microorganism and Hg methylation in soil environments.…”
Section: Introductionmentioning
confidence: 99%
“…Most Hg in soil is detected as ionic Hg 2+ species and shows relatively low toxicity, however, it still poses some environmental risk due to potential for Hg methylation followed by bioamplification in soilplant systems (Meng et al 2010;Liu et al 2012). Earlier studies have examined microbial methylation of Hg in estuarine, wetland, and freshwater sediments (Gilmour et al 1992; Heyes et al 2006;Duran et al 2008;Todorova et al 2009), but little attention to date has been paid to the linkage between specific types of microorganism and Hg methylation in soil environments.…”
Section: Introductionmentioning
confidence: 99%
“…However, whether the genes contribute a selective advantage related to Hg concentration or toxicity remains unclear (20). Moreover, the effects of environmental factors on the community that possesses the genes are completely unknown, although distribution patterns of microorganisms are usually influenced by a variety of factors in the environment (e.g., environmental variables and spatial and time factors) (21)(22)(23)(24). Paddy soils represent a typical freshwater environment that usually produces anaerobic conditions attributed to oxygen depletion after flooding (25), in which inorganic Hg(II) may be methylated by some anaerobic microorganisms (26).…”
mentioning
confidence: 99%
“…These results showed that different nutrient fertilizer led to major changes in the relative abundance of particular bacterial communities (Miransari, 2011). Both long‐term and short‐term studies have found that the abundance of Acidobacteria decreased significantly with the increase of N fertilizer application, which was closely associated with soil pH value (Liu, Li, et al., 2020), while, in our study, the relative abundance of Acidobacteria , serving as typically oligotrophic bacteria in the recommended NPK fertilization, was higher than that in other fertilization, which was in contradiction with previous research (Eo & Park, 2016; Islam et al., 2012). This may be related to the increase in the special subgroup function of Acidobacteria , which, in terms of genus, were unclassified Subgroup 3 , unclassified Subgroup 6 , unclassified Subgroup 17 , and uncultured Desulfovirga sp .…”
Section: Discussionmentioning
confidence: 99%